Evaluation of Antioxidant and Hepatoprotective Activities of Moringa oleifera Lam. Leaves in Carbon Tetrachloride-Intoxicated Rats - Dharmendra Singh; Priya Vrat Arya; Ved Prakash Aggarwal; Radhey Shyam Gupta (MDPI AG, 2014)
The antioxidant and hepatoprotective activities of the extract of Moringa oleifera leaves were investigated against CCl4-induced hepatotoxicity in rats. Hepatotoxic rats were treated with ethanol extract of Moringa oleifera for a period of 60 days at the following three dose levels; 100, 200 and 400 mg/kg body weight/day, orally. The activities were studied by assaying the serum marker enzymes like SGOT, SGPT, GGT, LDH, ALP, ACP, as well as total bilirubin, total protein and albumin in serum concomitantly with the activities of LPO, SOD, CAT, GSH, GR and GPx in liver. The activities of all parameters registered a significant (p ≤ 0.001) alteration in CCl4 treated rats, which were significantly recovered towards an almost normal level in rats co-administered with M. oleifera extract in a dose-dependent manner. All the biochemical investigations were confirmed by the histopathological observations and compared with the standard drug. silymarin. Results suggest that the antioxidant and hepatoprotective activities of M. oleifera leaves are possibly related to the free radical scavenging activity which might be due to the presence of total phenolics and flavonoids in the extract and/or the purified compounds β-sitosterol, quercetin and kaempferol, which were isolated from the ethanol extract of M. oleifera leaves.